Transition from growth point policy to liberal urban development in Zimbabwe: The emergence of Ruwa Town, 1980–1991 - Terence T. Muzorewa; Mark Nyandoro (African Online Scientific Information Systems (Pty) Ltd t/a AOSIS, 2023)
This article traces the transition from growth point policy to liberal development in the emergence of Ruwa Town in Zimbabwe from independence in 1980 to 1990/1991 when the town was declared an urban area under the administration of the Ruwa Local Board. In this period, there was a dire need for urban infrastructure (catalysed by a boom in urban population) in what was originally a commercial farming area. The article also analyses the role of private– public sector partnerships in promoting urban development. It contends that the establishment of Ruwa Growth Point and the town is closely associated with the rise of Private Land Developer Companies (PLDCs) in Zimbabwe. It further argues that all post-colonial established towns in Zimbabwe emerged out of the Government’s direct investment initiated under the growth centre policy. However, the development of Ruwa was not influenced by the Government, but by a transition from the State-led growth point policy to a liberal urban development approach, which involved public–private partnerships in infrastructural development and facilitation of public amenities. The economic liberalisation process adopted by the country in the early 1990s weakened the growth point policy and gave private actors leverage to enter the urban land market, which was originally monopolised by the Government. The failure of the Government-led growth point policy and the local authorities’ incapability to finance infrastructure development to improve service delivery forced the Ruwa Local Board to seek partnerships with PLDCs. The post-colonial State’s acquiescence to draw on the services provided by PLDCs demonstrates that the companies were effective instruments in ensuring the success of the liberal urban development strategy